2006
DOI: 10.1007/s10856-006-9678-8
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of slime producing Staphylococcus epidermidis strains to PVC and diamond-like carbon/silver/fluorinated coatings

Abstract: Staphylococcus epidermidis has emerged as a pathogen associated with infections of implanted medical devices. Bacterial adhesion is a crucial step in infection on biomaterial surfaces. To quantitatively determine the relationship between poly (vinyl chloride) (PVC) surface properties and bacterial adhesion, we have compared attachment of slime-producing S. epidermidis strains on PVC and various coatings under flow conditions. Bacterial adhesion and colonization was quantified by counting the viable organisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 29 publications
3
61
0
5
Order By: Relevance
“…Glass, Plexiglas (polymethylmethacrylate), and polyvinyl chloride (PVC) plates (30 by 30 cm), with different degrees of surface hydrophilicity (glass Ͼ Plexiglas Ͼ PVC) according to water contact angle measurements obtained previously (26,50), were used as test surfaces. So that data could be compared, a construct similar to that used in a previous experiment (15) was employed to deploy the surfaces in seawater at a depth of 1 m below the water surface near Wheat Island off the Qingdao coast (36.31°N, 120.25°E) on 23 May 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Glass, Plexiglas (polymethylmethacrylate), and polyvinyl chloride (PVC) plates (30 by 30 cm), with different degrees of surface hydrophilicity (glass Ͼ Plexiglas Ͼ PVC) according to water contact angle measurements obtained previously (26,50), were used as test surfaces. So that data could be compared, a construct similar to that used in a previous experiment (15) was employed to deploy the surfaces in seawater at a depth of 1 m below the water surface near Wheat Island off the Qingdao coast (36.31°N, 120.25°E) on 23 May 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Although the competing mechanisms remain unclear, a large body of data suggests that both physical and chemical modifications of a material surface can be engineered to limit bacterial colonization. [5][6][7][8][9][10]12,13,20,22 For example, as shown in Figure 1, coating surgical-grade titanium alloy with a synthetic PEM of PAA and PAH reduced colony density of waterborne S. epidermidis bacteria by orders of magnitude after immersion in 10 7 bacteria/mL. Reduced colonization over both 2 and 4 h incubation timescales is relevant to medical procedure durations involving, for example, cardiac assist and orthopedic implant devices.…”
Section: Bacterial Colonization Can Be Reduced By Materialsmentioning
confidence: 99%
“…The presence of oxygen has been reported to be advantageous for biological activity. 54 Although some reports have found that fluorine can enhance bacterial adhesion on the surface of biomaterials, 55,56 others have reported that fluorine shows antibacterial ability. 57,58 Our data indicate that the roughness of both TiO 2 nanotube surfaces was higher than that of the two control samples.…”
mentioning
confidence: 99%